The effect of heat treatment on the corrosion resistance of power equipment parts - Vahrusheva, Vera; Hlushkova, Diana; Volchuk, Volodymyr; Nosova, Tetyana; Mamhur, Stella; Tsokur, Natalia; Bagrov, Valeriy; Demchenko, Sergey; Ryzhkov, Yuri; Scrypnikov, Victor (Харківський національний автомобільно-дорожній університет, 2022)
For the manufacture of parts and assemblies of the turbopump unit of details of power equipment, welded joints with corrosion resistant steels and heat-resistant alloys are used, requiring various modes heat treatment to achieve the required level of mechanical properties. In the manufacture of parts and assemblies of details of power equipment at the machine-building enterprises of Ukraine, it became necessary to replace semi-finished products. It is necessary to replace sheet products from high-alloy alloys ХН67МВТЮ and 06Х15Н6МВФБ with one alloy with a high complex of physical and mechanical characteristics. In the work, as a replacement for the applied heat-resistant alloys, Inconel 718 alloy welded to 316L steel. Samples of welded joints, processed according to the recommended mode, showed increased corrosion resistance.
Вплив термічного оброблення на корозійну стійкість деталей енергетичного обладнання
Keywords: heat resistant alloy; corrosion resistance; intergranular corrosion; welding; structure; soldering; жароміцний сплав; корозійна стійкість; міжкристалітна корозія; зварювання; структура; паяння; 620.175.2: 669.15; 10.30977/BUL.2219-5548.2022.97.0.24